Stock Return Analysis in Monetary Uncertainty - Risma Rinarta; Mahameru Rosy Rochmatullah (Paradoks : Jurnal Ilmu Ekonomi, 2026)
This research boldly investigates how inflation, interest rates, and exchange rates influence the stock returns of consumer non-cyclicals firms in the food and beverage sector listed on the Indonesia Stock Exchange from 2021 to 2024. Utilizing a quantitative methodology, the study relies on secondary data sourced from corporate financial disclosures and authoritative macroeconomic reports. The sample selection employed purposive sampling and was rigorously analyzed using multiple linear regression, including evaluations of classical assumptions, t-tests, F-tests, and assessments of the coefficient of determination. The findings reveal that inflation has a positive and significant effect on stock returns, suggesting that moderate inflation may signal a recovery in demand and firms' ability to adapt their pricing. In contrast, interest rates demonstrate a negative and significant impact on stock returns, suggesting that increased capital costs and the appeal of risk-free assets tend to hinder stock performance. The exchange rate positively and significantly affects stock returns, indicating that the market perceived currency fluctuations during the study period as opportunities to enhance competitiveness and industrial adaptation. These results affirm that macroeconomic elements critically shape investor expectations and stock performance in defensive sectors, making them vital considerations for investment strategies and corporate management decisions.